Synthetic SARS-CoV-2 (2019-nCoV), MERS-CoV and SARSr-CoV vaccine : A comparative computational analysis to propose candidate epitopes - Kouyate, Modibo; Sangare, Modibo; Sacko, Brahima; Haidara, Mohamed; Sidibe, Oumar (My University, 2020)
Background: Coronaviruses are normally specific to an animal taxon as host, mammals or birds depending on their species; however, these viruses can sometimes change host as a result of mutation. The HCoV-229E is one of six human coronaviruses that include HCoV-NL63, HCoV-OC43, HCoV-HKU1, MERS-CoV and SARSr-CoV (SARSr-CoV-1 and SARS-CoV2) and is distributed globally. MERS-CoV and SARS-CoV-2 could persist on inanimate surface like (metal, glass or plastic for up to nine days) (Huang, C.-L, 2020). Preventive measures and drug treatment with hydrochloroquine are useful, but a good effective vaccine may be needed to stop propagation of the covid-19 pandemic. The aim of our study was to identifiy vaccine candidate epitopes by bioinformatics approaches. Materials and Method: The complete genomic sequences of SARS-CoV-2 were obtained from 2019 Novel Coronavirus Resource (2019nCoVR) and two databases, including the National Center for Biotechnology Information (NCBI) Global Initiative on Sharing All Inﬂuenza Data (GISAID) and TAURAU/T-bio-infoserver for online bioinformatics. we will provide a brief review of viral origin, compare the sequencing data for conserved region identification, his commonest protein domain( target binding site) and consensus motif design for an potential candidate molecule (epitope) prurposition for treatment strategies for the newly identified 2019-nCoV , SARSr-CoV strain and MERS-CoV. Results: Interestingly, sequence comparison between SARS-CoV-2 and another strain revealed that the residues present in the receptor-interacting motive are highly conserved with 70 % identity. we funded five important amino acids ( L455, Y473, N479, F486, Q493) on the receptor binding domain from spike proteins responsible of contact between virus and horst . In the SARS-CoV_ RBD are present residues (D480, and T487) that allowed the interspecies infection. However, in SARS-CoV-2, slight modification of some residues could improve the interaction with the human cellular receptor: L455, F486, Q493, and N501. In SARS-CoV, two main residues (479 and 487) have been associated to the recognition of the human ACE2 receptor. In the SARS-CoV-2, the residues corresponding to N479 correspond to Q493 and T487 to N501. These changes in the SARS-CoV-2 represent energetically favorable changes for the interaction with the receptor. we identified the sequences of amino acids that are well conserved across many coronaviruses including 2019nCoV and other strains, the motif KRSFIEDLLFNKVTLADAGF was found to be particularly well-conserved in this study and corresponds to the region around one of the known cleavage sites of the SARS virus that are believed to be required for virus activation for cell entry. This sequence motif and surrounding variations formed the basis for proposing a specific synthetic vaccine epitope this finding can make related likely rigid small molecule candidates and binding targets. Conclusion: This study provides information and opportunities for biological confirmation. The work can nevertheless be described in bioinformatics terms, and easily replicated by others, although new data and research on Covid-19 are emerging and evolving at an explosive rythm.
Keywords: 2019-nCoV; COVID-19; épitopes; MERS-CoV; RBD; SARS-CoV; zoonose